2011
DOI: 10.1001/archinternmed.2010.540
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Guided Care Teams on the Use of Health Services

Abstract: Background The effect of interdisciplinary primary care teams on the use of health services by patients with multiple chronic conditions is uncertain. This study aimed to measure the effect of guided care teams on multimorbid older patients’ use of health services. Methods Eligible patients from 3 health care systems in the Baltimore, Maryland–Washington, DC, area were cluster-randomized to receive guided care or usual care for 20 months between November 1, 2006, and June 30, 2008. Eight services of a guided… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
213
0
4

Year Published

2011
2011
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 205 publications
(222 citation statements)
references
References 20 publications
5
213
0
4
Order By: Relevance
“…Given the concentration of health expenditures in a subset of complex patients, 5 improving the efficiency of care delivery to this group may help contain costs. [6][7][8][9][10][11][12] Identifying complex, high-risk primary care patients is an important first step that allows healthcare systems to better allocate resources and target interventions. Current quantitative methods for identifying the complex patients at highest risk for suboptimal future clinical quality and utilization outcomes rely primarily on diagnosis-based and utilization-based algorithms to predict future utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Given the concentration of health expenditures in a subset of complex patients, 5 improving the efficiency of care delivery to this group may help contain costs. [6][7][8][9][10][11][12] Identifying complex, high-risk primary care patients is an important first step that allows healthcare systems to better allocate resources and target interventions. Current quantitative methods for identifying the complex patients at highest risk for suboptimal future clinical quality and utilization outcomes rely primarily on diagnosis-based and utilization-based algorithms to predict future utilization.…”
Section: Introductionmentioning
confidence: 99%
“…Notably, prior subgroup analysis had shown that Guided Care was significantly more effective in reducing the use of skilled nursing facility admissions and days in the Kaiser Permanente group when compared to the other practice models. 12 That study also showed a trend toward reduced hospital admissions, 30-day readmissions, hospital days, and emergency department visits, although this did not achieve statistical significance. It may be that a streamlined electronic medical records program, a health system that encompasses a complete array of health care services, and possibly a culture that emphasizes prevention and avoidance of unnecessary care, is more equipped to implement and reap the full benefits of the Guided Care model.…”
mentioning
confidence: 85%
“…Cost reductions have been found related to many outcomes important to policymakers, including decreased hospital costs; decreased hospitalization, emergency department, and intensive care unit rates; reduction in 30-day readmission rates; and decreased hospital mortality. [12][13][14][15][16][17][18][19][20][21][22][23][24][25][26][27] Most successful models involve some degree of care management. Some are focused on increasing safety and patientcentered care in the inpatient setting, such as Acute Care for the Elderly (ACE) units, the Hospital Elder Life Program (HELP), Nurses Improving Care to Health System Elders (NICHE), and palliative care consult services.…”
Section: Models Of Carementioning
confidence: 99%
“…Geriatric Resources for Assessment and Care of Elders (GRACE) and Guided Care are two examples of interdisciplinary programs that have established a track record for increasing coordination of care for older patients with multiple chronic conditions. 26,27 Much of the intent of these programs is to overcome both the balkanized health system-hospital, outpatient practice, nursing home, assisted living, hospice-and the disconnect between medical disciplines-primary care providers, hospitalists, cardiologists, oncologists, surgeons, and other specialists-that can frustrate and confound patients. Because there is no payment mechanism to support them, the ''best practices,'' exemplified in these models and others, have been difficult to scale up and have not reached the large numbers of patients who could benefit from them.…”
Section: Models Of Carementioning
confidence: 99%